Gel flow generated by air current in vicinity of porous surfaces - Mateescu Ciprian; Cristea Doru-Daniel; Tanase Nicoleta–Octavia; Balan Corneliu (E3S Web of Conferences)
Mechanical ventilation is a critical intervention for intubated patients suffering from respiratory complications, such as excess mucus accumulation in the trachea, which can obstruct airflow. In this study, we investigate the impact of a Fresubin-water emulsion (1g/50ml), simulating mucus, on airflow resistance in a square-profile tube representing a simplified tracheal segment. The hypothesis predicate that the emulsion will increase airflow resistance under mechanical ventilation, mimicking the obstructive effects of mucus in patients. A computational fluid dynamics (CFD) analysis was employed to evaluate the airflow characteristics within the tube, focusing on velocity profiles and pressure drop. The results confirmed that the viscoelastic properties of the emulsion significantly altered airflow behavior, producing non-uniform velocity distributions and an elevated pressure gradient along the tube. These findings suggest that the emulsion effectively replicates the behavior of mucus in the trachea, offering valuable insights for improving mechanical ventilation strategies in patients with respiratory obstructions.